Transient receptor potential vanilloid subtype 1: A potential therapeutic target for fibrotic diseases - Peng, Guangxin; Tang, Xiaoling; Gui, Yang; Yang, Jing; Ye, Lifang; Wu, Liuyang; Ding, Ya hui; Wang, Lihong (Frontiers in Physiology, 2022)
The transient receptor potential vanilloid subtype 1 (TRPV1), belonging to the TRPV channel family, is a non-selective calcium-dependent cation channel that is implicated in several pathophysiological processes. Collagen, an extracellular matrix component, is known to continuously accumulate and may lead to destruction of tissue structure, organ dysfunction, and organ failure. Increasing evidence indicates that TRPV1 plays a role in the development and occurrence of fibrotic diseases including myocardial, renal, pancreatic, and corneal fibrosis. However, the mechanism through which TRPV1 regulates fibrosis remains unclear. The purpose of this review is to highlight the comprehensive role that TRPV1 plays in the regulation of pro-fibrotic responses and the potential of TRPV1 to act as a therapeutic target in fibrotic diseases as well as the different signaling pathways associated with TRPV1 and fibrosis.